An Open-Label, Randomized, Double-Arm Clinical Trial to Compare the Effectiveness and Safety of Super Bioavailable Itraconazole Capsules and Itraconazole Capsules in the Management of Dermatophytosis in India - Shenoy M; Dhoot D; Mahajan H; Barkate H (Dove Medical Press, 2021)
Manjunath Shenoy,1,2 Dhiraj Dhoot,3 Harshal Mahajan,3 Hanmant Barkate3 1Department of Dermatology, Yenepoya Medical College, Deralakatte, Mangalore, India; 2Omega Hospital, Mangalore, Karnataka, India; 3Global Medical Affairs, Glenmark Pharmaceuticals Ltd, Mumbai, Maharashtra, IndiaCorrespondence: Dhiraj DhootGlobal Medical Affairs, Glenmark Pharmaceuticals Ltd, B D Sawant Marg, Andheri (E), Mumbai, Maharashtra, 400099, IndiaTel +91 9619811219Email dhiraj.dhoot@glenmarkpharma.comPurpose: A new oral formulation of itraconazole, called super bioavailable itraconazole (SBITZ), has been launched in India, exhibiting greater bioavailability than conventional itraconazole (CITZ). No clinical studies on its effectiveness and safety in dermatophytosis in comparison with CITZ have been conducted in India. Hence, the aim of this clinical study was to compare the effectiveness and safety of SBITZ capsules and CITZ capsules in dermatophytosis.Patients and Methods: This was an open-label, randomized, double-arm clinical study in which 70 patients (≥ 18 years of age) of either gender and diagnosed with tinea cruris, tinea corporis, and/or tinea faciei were included. The study was divided into two parts, the first part comprising a treatment period of 4 weeks and the second part an observation period for recurrence, comprised of another 4 weeks, thus making an entire study duration of 8 weeks.Results: Of the 70 patients enrolled in this study, 59 (33 patients in the CITZ group and 26 patients in the SBITZ group) were included in the final analysis. In both groups, most patients were diagnosed with tinea cruris et corporis, with five or more lesions. At week 4, 11 patients (33.33%) and 17 patients (65.38%) had achieved complete cure (p< 0.05), whereas 22 patients (66.67%) and 22 patients (84.61%) had achieved mycological cure (p=0.14), in the CITZ and SBITZ groups, respectively. During the observation period, recurrence was seen in 1/11 and 4/17 completely cured patients in the CITZ and SBITZ groups, respectively (p=0.15). A significant difference was noted in resolution of symptoms as well as lesions of dermatophytosis in the SBITZ group (p< 0.05). Both treatments were found to be safe and well tolerated.Conclusion: In the light of real-world evidence on effectiveness and safety, SBITZ should be considered as a potent therapeutic choice to effectively control the current menace of dermatophytosis in India.Keywords: dermatophytosis, super bioavailable itraconazole, conventional itraconazole, India